INTEGRATING ECOSYSTEM-WIDE FLOURISHING IN BANKING RISK MANAGEMENT: A Comparative Study of Microfinance Case Study and Conventional Banking - Christabel Sylvie Sianipar; Adi Firman Ramadhan; Jan Noeverman; Frank Gruben (Diponegoro Journal of Accounting, 2025)
This thesis investigates how ecosystem-wide flourishing (EWF), defined as the well-being of individuals, organizations, and regions, can be integrated into banking risk management to enhance financial resilience. Using a qualitative comparative approach, it examines two cases: the Love in Action microfinance study and a semi-structured interview with a senior leader from a conventional bank. Drawing on stakeholder theory, the triple bottom line, resilience theory, and financial resilience frameworks, the research explores how human-centered practices influence risk assessment and organizational performance. Findings reveal that while microfinance institutions embed flourishing through formal agreement structures and cultural rituals, conventional banks primarily rely on financial indicators and informal assessments, overlooking critical relational and leadership dynamics. The study concludes that integrating EWF into banking practices can improve stakeholder trust, reduce systemic risks, and support long-term financial sustainability. Practical recommendations are provided for banks and SMEs to develop structured tools, leadership evaluations, and inclusive risk frameworks that align with sustainable development goals.